2017
DOI: 10.1667/rr14646.1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine Translocation after Radiosurgery in an Animal Model of Arteriovenous Malformation

Abstract: Phosphatidylserine (PS) is asymmetrically distributed across the plasma membrane, located predominantly on the inner leaflet in healthy cells. Translocation of PS to the outer leaflet makes it available as a target for biological therapies. We examined PS translocation after radiosurgery in an animal model of brain arteriovenous malformation (AVM). An arteriovenous fistula was created by end-to-side anastomosis of the left external jugular vein to the common carotid artery in 6-week-old, male Sprague Dawley ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…While PS targeting in tumors has been more avidly pursued in the context of cancer immunotherapy [35], it has been investigated as a radiation-stimulated target for vascular infarction in brain AVMs [36][37][38][39][40]. Thorpe and colleagues demonstrated that translocation of this phospholipid to the surface of tumor vessels could be enhanced in response to oxidative stress, via stimulation by growth factors, hydrogen peroxide, and ionizing radiation [28,41,42].…”
Section: Phosphatidylserine (Ps)mentioning
confidence: 99%
“…While PS targeting in tumors has been more avidly pursued in the context of cancer immunotherapy [35], it has been investigated as a radiation-stimulated target for vascular infarction in brain AVMs [36][37][38][39][40]. Thorpe and colleagues demonstrated that translocation of this phospholipid to the surface of tumor vessels could be enhanced in response to oxidative stress, via stimulation by growth factors, hydrogen peroxide, and ionizing radiation [28,41,42].…”
Section: Phosphatidylserine (Ps)mentioning
confidence: 99%
“…To date, various endogenous markers have been identified on tumor vasculature and investigated in mouse tumor infarction models (reviewed in [ 1 ]). However, limitations to endogenous biomarker discovery in brain arteriovenous malformations (AVMs) have led to the use of ionizing radiation as a priming agent for target generation in this context [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation damage sets off a cascade of cellular events in endothelial cells that can alter the molecules or proteins at the cell surface (surfaceome) [ 4 , 5 , 15 , 16 ]. Surface exposure of common inflammatory markers such as phosphatidylserine (PS), vascular cell adhesion molecule 1 (VCAM-1) and intercellular adhesion molecule 1 (ICAM-1) have been previously investigated as radiation-stimulated targets in an AVM animal model [ 6 , 7 , 13 , 17 ]. However, their frequent exposure in response to other biological stimuli may reduce targeting specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular targeting was first described in cancer therapy to deliver thrombotic agents for tumor vessel destruction that capitalizes on the inherent molecular differences between tumor endothelium and normal, healthy endothelium that can be used to target agents selectively to the site of disease [3,4]. To date, no inherent, discriminatory vascular markers have been identified on human AVMs, hence we proposed that a combination of focused radiosurgical priming and vascular targeting may be an effective approach for AVM cure [5,6,7,8,9,10,11]. Radiation has previously been used to enhance target expression on tumor vasculature [12,13].…”
Section: Introductionmentioning
confidence: 99%